Chemical composition of Cymbopogon flexuosus (Poaceae) essential oil, its insecticidal and repellency activity against Sitophilus zeamais (Coleoptera:Curculionidae) - Mota Filho, Tarcísio Marcos Macedo [UNESP] (2022)
Sitophilus zeamais (Coleoptera: Curculionidae) is a common pest in stored corn grains [Zea mays (Poaceae)]. Synthetic insecticides are effective to control S. zeamais; however, they can develop resistant insects and are toxic to humans and animals. Compounds with insecticidal potential from plants are alternatives for pest control. This study identified the chemical composition of Cymbopogon flexuosus (Poaceae) essential oil, its insecticidal and repellency activity against S. zeamais. The major chemical constituent found in the essential oil of C. flexuosus was citral (88%). The data showed that the essential oil of C. flexuosus and citral showed better insecticidal and repellent activity than the commercial insecticide Actellic used as positive control. The 100% mortality of S. zeamais was obtained at doses of 50 and 44 µL of essential oil and citral, respectively. The highest repellent activity was obtained with 40 and 50 µL of essential oil and 35.2 and 44 µL of citral, respectively, and the lowest with commercial insecticide Actellic. The lethal dose (LD50) was 18.10 and 18.95 µL for essential oil and citral, respectively. The lethal time was lower at doses of 44 and 50 µL essential oil and citral, respectively, and higher with the commercial insecticide. The insecticidal and repellent action of the essential C. flexuosus and its major compound confirms the potential of producing new biopesticide for the control of S. zeamais in Integrated Pest Management (IPM) programs in stored grains.